INSTRUCTION OF VOCABULARY AT THE HIGHER SECONDARY LEVEL IN BANGLADESH: INTEGRATION OF COMMUNICATIVE LANGUAGE TEACHING (CLT) WITH VOCABULARY TASKS - Rahman Bipasha, Sharmin (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
The research aimed to enhance vocabulary instruction at the upper secondary level in Bangladesh by integrating Communicative Language Teaching with vocabulary activities. This study examined the common vocabulary tasks associated with Communicative Language Teaching (CLT) for grades 11-12, current vocabulary learning techniques and tasks, the challenges that impede the effective application of these methods, and the potential strategies for enhancing vocabulary acquisition, focusing on key factors that could improve students' English vocabulary. A mixed-methods approach was used for data collecting and analysis. The research included surveys from 100 students, interviews with 10 instructors, and classroom observations to gather data. The cluster random sampling approach was used to select samples for this research, focusing on a group of current (Higher Secondary Certificate) HSC-level students and instructors. The objective data acquired via questionnaires were statistically evaluated using descriptive statistics expressed as percentages, whereas the interview and classroom observation data were presented in narrative form via comments. The study's results suggested that the alignment of CLT and vocabulary activities significantly influenced the development of students' vocabulary. Research indicated that both vocabulary activities and the principles of CLT are extensively used by students and educators to enhance vocabulary acquisition. The research identified common issues in vocabulary acquisition and proposed many solutions to facilitate comprehensive vocabulary learning.